2016
DOI: 10.3390/s16122068
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Impedance Monitoring of C2C12 Myoblast Differentiation on an Indium Tin Oxide Electrode

Abstract: Electrical cell-substrate impedance sensing is increasingly being used for label-free and real-time monitoring of changes in cell morphology and number during cell growth, drug screening, and differentiation. In this study, we evaluated the feasibility of using ECIS to monitor C2C12 myoblast differentiation using a fabricated indium tin oxide (ITO) electrode-based chip. C2C12 myoblast differentiation on the ITO electrode was validated based on decreases in the mRNA level of MyoD and increases in the mRNA level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…To overcome hurdles in studying myogenesis, other tools have been designed to assess myoblast differentiation in real-time based on live cell monitoring. These tools include assessment of physical properties and function such as contractility through displacement analysis [ 36 ], skeletal muscle thickness [ 45 , 46 ] and myoblast differentiation [ 46 ] through electrical impedance. Additionally, multiple imaging modalities have been applied to assess muscle biology, including bioluminescence imaging for luciferase tagged cell transplantation [ 47 ], second harmonic generation (SHG) imaging to quantify muscle striation patterns [ 48 , 49 ], MRI to assess oxidative phosphorylation in muscle [ 50 ], and multi-photon imaging for the assessment of myoblast oxidation level [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…To overcome hurdles in studying myogenesis, other tools have been designed to assess myoblast differentiation in real-time based on live cell monitoring. These tools include assessment of physical properties and function such as contractility through displacement analysis [ 36 ], skeletal muscle thickness [ 45 , 46 ] and myoblast differentiation [ 46 ] through electrical impedance. Additionally, multiple imaging modalities have been applied to assess muscle biology, including bioluminescence imaging for luciferase tagged cell transplantation [ 47 ], second harmonic generation (SHG) imaging to quantify muscle striation patterns [ 48 , 49 ], MRI to assess oxidative phosphorylation in muscle [ 50 ], and multi-photon imaging for the assessment of myoblast oxidation level [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ITO electrode, which was established in our previous studies [22,26], was prepared as shown in Figure 1. The brief fabrication process of the ITO electrode-based cultureware is as follows.…”
Section: Fabrication Of the Ito Electrode-based Culturewarementioning
confidence: 99%
“…For the impedance monitoring of cells, the established experimental setup [22,26] was utilized, which consisted of the digital lock-in-amplifier (SR830; Stanford Research Systems, Sunnyvale, CA, USA), multiplexer, and LabVIEW program. The amplitude of the current flowing through the cells on the electrode was restricted to below 1 µA to minimize electrical effects on the cells.…”
Section: Impedance Measurement Of Cells On the Rgo-aunp/ito Electrodementioning
confidence: 99%
See 1 more Smart Citation
“…Muscle cells respond to electric fields and induce the contraction of muscle tissue. Thus, the local electric field generated by ZnO NSs would potentially improve the regeneration and rehabilitation of muscle tissue, with several future applications in chronic illnesses such as muscle atrophy, wasting and aging [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%